Identifikasi Jamur Endofit Pada Tanaman Obat Tradisional Di Sulawesi Selatan - Dito Anurogo; Rezqiqah Aulia Rahmat; Rahmat Pannyiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Endophytic fungi are microorganisms that live within plant tissues without causing disease symptoms. This study aimed to identify endophytic fungi associated with traditional medicinal plants in South Sulawesi that may produce bioactive compounds. The research was exploratory in nature, isolating fungi from leaves and stems using Potato Dextrose Agar (PDA) medium, and identifying them based on macroscopic and microscopic morphological characteristics. The results revealed the presence of several genera of endophytic fungi, including Aspergillus, Penicillium, Fusarium, and Trichoderma. These findings indicate the significant potential of endophytic fungi in the development of biotechnology-based traditional medicines.